Emotional branding analysis for the Korean Drama-based tourism locations - Amida Yusriana; Devi Purnamasari; Nalal Muna (Faculty of Social and Political Science, Universitas Airlangga, 2019)
City branding is an effort to build a particular image of a city. Semarang is one of Indonesia’s big cities that has not yet succeeded in finding the right brand to represent it. The researcher has conducted a pilot research study that aims to build Semarang’s city branding as The Cinematic City. It is due to Semarang’s background of often becoming a shoot location for famous movies. South Korea is well known because of its pop cultures, such as drama. Drama is one of the main factors that contribute to the increasing number of foreign visitors. They mostly visit popular drama shooting locations as their destinations. These kinds of tourism site are successful at developing emotional branding in the visitor’s minds. Looking at the similarity of South Korea and Semarang will help Semarang to learn a lot from what South Korea has done. This research aims to analyse how emotional branding represented through the Korean drama-based tourism site gimmicks. This research used the Emotional Branding theory by Marc Gobe. It assumed that emotional bonding is an essential thing in terms of engaging the customer and product in a particular phase. The main subjects of this research are the gimmicks in Nami Island. The result shows that the Relationship Aspect fulfilled by changing the theme and properties according to the season. For the Five Senses Experience, it only employs the sense of sight and touch by creating many gimmicks that can be a photo-taking hot spot. The Imagination aspect fulfilled by the unique design of the Emotional Identity put forward, such as the snowman.